If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13s + 8)(5s + -2) = 0 Reorder the terms: (8 + 13s)(5s + -2) = 0 Reorder the terms: (8 + 13s)(-2 + 5s) = 0 Multiply (8 + 13s) * (-2 + 5s) (8(-2 + 5s) + 13s * (-2 + 5s)) = 0 ((-2 * 8 + 5s * 8) + 13s * (-2 + 5s)) = 0 ((-16 + 40s) + 13s * (-2 + 5s)) = 0 (-16 + 40s + (-2 * 13s + 5s * 13s)) = 0 (-16 + 40s + (-26s + 65s2)) = 0 Combine like terms: 40s + -26s = 14s (-16 + 14s + 65s2) = 0 Solving -16 + 14s + 65s2 = 0 Solving for variable 's'. Factor a trinomial. (-8 + -13s)(2 + -5s) = 0Subproblem 1
Set the factor '(-8 + -13s)' equal to zero and attempt to solve: Simplifying -8 + -13s = 0 Solving -8 + -13s = 0 Move all terms containing s to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -13s = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -13s = 0 + 8 -13s = 0 + 8 Combine like terms: 0 + 8 = 8 -13s = 8 Divide each side by '-13'. s = -0.6153846154 Simplifying s = -0.6153846154Subproblem 2
Set the factor '(2 + -5s)' equal to zero and attempt to solve: Simplifying 2 + -5s = 0 Solving 2 + -5s = 0 Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5s = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5s = 0 + -2 -5s = 0 + -2 Combine like terms: 0 + -2 = -2 -5s = -2 Divide each side by '-5'. s = 0.4 Simplifying s = 0.4Solution
s = {-0.6153846154, 0.4}
| (5a^2-a+4)(5a^2-a+4)= | | x+100=-2 | | X-2(x-1)=2x-5 | | .20b-.40=-2 | | 2(y-6)=3y-2(8-y) | | 3(2+x)=x+8 | | b^2-4b-45=0 | | -1.75v+1-3.3=-3.20 | | 2c^2=5c+3 | | 4x^2+28x+48=0 | | 7+2p-6=9p+8-6p | | 18=15y-(-2x+21) | | x+2x+.15x+.05=1.8 | | 5x+2x-3=-3x+10x+3 | | 2c^2-13c=7 | | (x-1)(x+6)= | | 5(x-3)+9=2x+3(-3+x) | | 4=y-3 | | 19-(2x+3)=2(x+3)+1 | | 3v^2-22v=16 | | 14x-8+3x-3=13x-3+3x | | 3x^2-22v=16 | | (x+8)(x+7)= | | .5x+.5+2.75x=10.25 | | 3-4y=7 | | 21x+9=4(4x+4)+5x-7 | | 2y^2-8-4y=y^2-2y | | 2x^2+16x+14=54 | | 0.25q+0.10(3q)=4.95 | | 4(6x+5)=24x+20 | | (4y+3)(y+6)=-4(4y+3) | | 2u^2+u+2=0 |